Calorific Value of Rubberwood Biomass Along the Tree - Quartey, Gladys Ama; Eshun, John Frank; Marfo, Eric Donkor (European Journal of Applied Sciences, 2022)
Rubberwood is one of the major plantation crops grown mainly in the Western Region of Ghana. They are mostly utilised for their latex. Rubber trees that are aged and low yielding can be cut down and properly utilised as fuelwood. In Ghana, there is a high demand for fuelwood in most domestic homes and rubberwood is one of the tree species with potential use as fuelwood. Even though gas has been promoted as an energy source for heating and cooking activities in Ghana, it remains expensive, and its affordability, therefore, remains out of reach of many people. Rubberwood, which is plantation grown can, therefore, be considered as fuelwood. In this study, the calorific values of rubberwood biomass from a plantation were determined using samples from the bottom, middle, branch, and top parts of the stem. The calorific values of rubber wood biomass from different sections of the tree were determined in accordance with standard laboratory methods using a bomb calorimeter. The calorific values obtained were 17.194 MJ/kg for the branch, 17.225 MJ/kg for the top, 17.595 MJ/kg for the middle, and 17.702 MJ/kg for the bottom. The trend of the values shows that the calorific value decreases from the bottom through the top of the stem to the branch. The calorific value of rubberwood was comparable to other high-performing tree species used for fuelwoods and therefore has the potential to be used for fuelwood.